STUDI IN VITROHUBUNGAN LOGARITMA KOEFISIEN PARTISI DENGAN IKATAN PROTEIN PLASMA DARIANTIDIABET TURUNAN SULFONIL UREA SEBAGAI BAHAN PEMBELAJARAN MATA KULIAH FARMASIFISIK - Irawan, Eka Deddy (Jurnal Pengembangan Pendidikan, 2006)
Abstract. This paper shows that oral antidiabeticSulfonil Ureic derivates (The first generation: Chlorpropamide, and the secondgeneration : Gliclazide, Glibenclamide & Glipizide) have logaritmicpartition coefficient value increased. The increased value in logaritmiccoeficient partition due to modification of chemical structure of suchcompounds. Such modification caused the polarity property of such compoundincreases, which in turn, increasing the logaritmic coeficient partition value.According to this paper that the chemical structure of antidiabet sulfunil ureicderivates play important role in protein plasm bonding in drug. This articlecan be used as laboratory practice or studied material on Physical Pharmacy. Keyword : InVitro Study, Oral antidiabetic Sulfunil Ureic derivates, logaritmic partitioncoeficient, protein plasm bonding.